1995
DOI: 10.1007/bf02638858
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the monoenoic fatty acid distribution in hydrogenated vegetable oils by silver‐ion high‐performance liquid chromatography

Abstract: A silver‐ion high‐performance liquid chromatography column (hexane/acetonitrile as solvent, ultraviolet detection) was used to analyze the fatty acid distribution (as fatty acid methyl esters) of a representative sample of hydrogenated oil. Fractions containingcis‐ andtrans‐18:1 isomers were readily separated. The positional fatty acid isomers were separated by rechromatographing these fractions. The elution order and percent compositions were compared with results obtained by gas chromatography. Of the Δ8 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

1997
1997
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 15 publications
0
26
0
1
Order By: Relevance
“…The Ag + -HPLC method, developed by Adlof et al [22] and refined and applied to CLA isomers by Sehat et al [19], was modified as follows: two analytical silver-impregnated HPLC columns were fitted in series (ChromSpher 5 Lipids, 4.6 mm i.d.6250 mm stainless steel; 5 lm particle size, Chrompack, Netherlands). The HPLC (Merck/Hitachi 655A-12 LC, L-5000 Controller) was equipped with a UV detector (Merck/Hitachi L 4 200 UV/VIS) and an operating system (Chromstar, version 3.20).…”
Section: + -Hplcmentioning
confidence: 99%
“…The Ag + -HPLC method, developed by Adlof et al [22] and refined and applied to CLA isomers by Sehat et al [19], was modified as follows: two analytical silver-impregnated HPLC columns were fitted in series (ChromSpher 5 Lipids, 4.6 mm i.d.6250 mm stainless steel; 5 lm particle size, Chrompack, Netherlands). The HPLC (Merck/Hitachi 655A-12 LC, L-5000 Controller) was equipped with a UV detector (Merck/Hitachi L 4 200 UV/VIS) and an operating system (Chromstar, version 3.20).…”
Section: + -Hplcmentioning
confidence: 99%
“…® column has, however, been used as a good alternative to Ag-TLC for preliminary isomer fractionation before GC analysis, and as a method for isolating most 18:1 positional isomers [70]. A collaborative study [86] showed that this methodology gives results that are as good, repeatable and reproducible as Ag-TLC as regards trans-18:1 fractionation prior to GC analysis.…”
Section: A Chromspher Lipidsmentioning
confidence: 99%
“…Using this column, procedures were developed to fractionate trans-and cis-monoenoic FAME by Ag-HPLC for further GC analyses of the two separate fractions [32,70]. This technique was used to determine the total trans-monoene content of PHVO and results were compared with data obtained by FTIR [32].…”
Section: Silver Nitrate Hplcmentioning
confidence: 99%
“…Maintenant des colonnes prêtes à l'emploi sont commercialisées. Une séparation des isomères du 18:1 a été décrite par Adlof [23] en utilisant celles-ci. De plus, les 7 isomères de l'acide α-linolénique ont été séparés et identifiés [24] en utilisant une colonne Nucleosil 5SA imprégnée au nitrate d'argent (Fig.…”
Section: Utilisation De Différentes Techniques Chromatographiques Pouunclassified